Validity and Reliability of the Anxiety Assessment Scale: A New Three-dimensional Perspective - Cem MALAKCIOGLU (Medeniyet Medical Journal)
Objective: Anxiety is inseparable from life due to its survival value. Up-to-date and multidimensional assessment of anxiety is necessary to develop effective interventions to cope with high anxiety levels. This study was conducted to examine the psychometrics of the Anxiety Assessment Scale (AAS). Methods: Data were collected between January and April 2021 from 756 students (42.9% males and 57.1% females) studying medicine at Istanbul Medeniyet University. Seven experts evaluated the items to detect content validity in the final application form. Both exploratory and confirmatory factor analyses (EFA and CFA) were used for construct validity. The Beck Anxiety Inventory was also applied for concurrent validity. Test-retest reliabilities were calculated within four weeks. IBM SPSS 25 and AMOS 24 were used for statistical analyses. Results: Data were suitable for factor analyses (Kaiser-Meyer-Olkin=0.800, chi-square=3018.854, df=45). The EFA showed the three-factor structure with 10 items, and 70.1% of the variance was explained. Factor loads of the items varied between 0.61 and 0.87; data-model fit was suitable (CFI=0.92, TLI=0.93, RMSEA=0.059, SRMR=0.046, chi-square/df=1.556) according to CFA. Concurrent scale validity was also confirmed by the Pearson correlation (r=0.167, p<0.01). The test-retest reliabilities (r) were all >0.5 (p<0.001). The Cronbach a coefficients were 0.845 (AAS), 0.770 (Physiological Tension=PT), 0.822 (Worrying=W), and 0.838 (Feeling Unsafe=FU). Conclusions: AAS is a reliable and valid measurement instrument to assess anxiety levels in three dimensions. AAS can be applied for research, psychological assessment, and other appropriate application purposes.